Externalised locking compression plate as an alternative to the unilateral external fixator : a biomechanical comparative study of axial and torsional stiffness - Ang, B. F. H. (2019)
Objectives: External fixators are the traditional fixation method of choice for contaminated open fractures. However, patient acceptance is low due to the high profile and therefore physical burden of the constructs. An externalised locking compression plate is a low profile alternative. However, the biomechanical differences have not been assessed. The objective of this study was to evaluate the axial and torsional stiffness of the externalised titanium locking compression plate (ET-LCP), the externalised stainless steel locking compression plate (ESS-LCP) and the unilateral external fixator (UEF). Methods: A fracture gap model was created to simulate comminuted mid-shaft tibia fractures using synthetic composite bones. Fifteen constructs were stabilised with ET-LCP, ESS-LCP or UEF (five constructs each). The constructs were loaded under both axial and torsional directions to determine construct stiffness. Results:The mean axial stiffness was very similar for UEF (528 N/mm) and ESS-LCP (525 N/mm), while it was slightly lower for ET-LCP (469 N/mm). One-way analysis of variance (ANOVA) testing in all three groups demonstrated no significant difference (F(2,12) = 2.057, p = 0.171). There was a significant difference in mean torsional stiffness between the UEF (0.512 Nm/degree), the ESS-LCP (0.686 Nm/degree) and the ET-LCP (0.639 Nm/degree), as determined by one-way ANOVA (F(2,12) = 6.204, p = 0.014). A Tukey post hoc test revealed that the torsional stiffness of the ESS-LCP was statistically higher than that of the UEF by 0.174 Nm/degree (p = 0.013). No catastrophic failures were observed. Conclusion: Using the LCP as an external fixator may provide a viable and attractive alternative to the traditional UEF as its lower profile makes it more acceptable to patients, while not compromising on axial and torsional stiffness.